2021
DOI: 10.1029/2021gh000442
|View full text |Cite
|
Sign up to set email alerts
|

Natural Gas Gathering and Transmission Pipelines and Social Vulnerability in the United States

Abstract: Midstream oil and gas infrastructure comprises vast networks of gathering and transmission pipelines that connect upstream extraction to downstream consumption. In the United States (US), public policies and corporate decisions have prompted a wave of proposals for new gathering and transmission pipelines in recent years, raising the question: Who bears the burdens associated with existing pipeline infrastructure in the US? With this in mind, we examined the density of natural gas gathering and transmission pi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 58 publications
0
15
0
1
Order By: Relevance
“…As behavioral medicine professionals, we must partner across communities and disciplines to generate evidence needed for legislative action and advocate for meaningful policy changes nationally and locally (including at our own institutions). For example, the construction of oil pipelines is concentrated near Indigenous communities, increasing health risks via environmental destruction, exposure to toxic chemicals, and increased risk of sexual violence [ 86–89 ]. Research on the short and long-term health, behavior, and quality of life consequences of proximity to fossil fuel infrastructure supports legislation banning new fossil fuel infrastructure development in communities targeted for marginalization [ 39 , 55 , 90 ].…”
Section: A Call To Action For Behavioral Medicinementioning
confidence: 99%
“…As behavioral medicine professionals, we must partner across communities and disciplines to generate evidence needed for legislative action and advocate for meaningful policy changes nationally and locally (including at our own institutions). For example, the construction of oil pipelines is concentrated near Indigenous communities, increasing health risks via environmental destruction, exposure to toxic chemicals, and increased risk of sexual violence [ 86–89 ]. Research on the short and long-term health, behavior, and quality of life consequences of proximity to fossil fuel infrastructure supports legislation banning new fossil fuel infrastructure development in communities targeted for marginalization [ 39 , 55 , 90 ].…”
Section: A Call To Action For Behavioral Medicinementioning
confidence: 99%
“…We broadly classify these burdens into three categories: safety, economic, and environmental/public health burdens. These burdens range from chronic to acute and likewise vary in severity, as has been documented for a variety of other EJ burdens. ,, …”
Section: Discussionmentioning
confidence: 81%
“…Several studies have now documented the burdens, benefits, and injustices of the oil and gas industry and its infrastructure. , These studies document the EJ impacts of oil and gas production, especially those related to fracking. Looking at the location of natural gas gathering and transmission pipelines, Emanuel et al found that counties with a high social vulnerability index (SVI) have higher pipeline concentrations than counties with a lower SVI. The SVI includes factors such as socioeconomic status, household composition and disability, nonwhite non-Hispanic population and language, and housing type and transportation .…”
Section: Introductionmentioning
confidence: 99%
“…74 Natural gas infrastructure, such as pipelines, compressor stations, and power plants, are often located in the middle of low-income neighborhoods. [75][76][77] In areas where natural gas is used for cooking, historically marginalized populations are disproportionately exposed to gas leaks, and repair times are often longer in communities of lower socioeconomic status. 78 Other aspects of the natural gas development process have not been robustly assessed with respect to environmental justice.…”
Section: Environmental Justicementioning
confidence: 99%